2013
DOI: 10.1179/1879139513y.0000000099
|View full text |Cite
|
Sign up to set email alerts
|

Reducibility of nickeliferous limonitic laterite ore from Central Anatolia

Abstract: Limonitic nickel laterite from Sivrihisar reserve in Turkey was reduced at 700-1100uC by the addition of 5?74, 8?61 and 11?48 wt-% coal under an argon atmosphere. The run-of-mine ore and the reduced samples were studied using X-ray diffraction. The metallisation of Fe was found to be limited up to 900uC, but increased rapidly at higher temperatures. The metallisation of Ni and Co increased when the temperature was increased from 700 to 800uC, almost levelled off up to 900uC and then increased up to 1100uC. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Subsequently, the dehydration of goethite occurs through Reaction (7). However, NiCl 2 did not precipitate as an oxide, because the precipitation of FeCl 4 -in the form of Fe 2 O 3 is more thermodynamically favorable than the precipitation of Ni 2+ as NiO. So the pressure hydrochloric-acid leaching had also realized selective pressure leaching.…”
Section: Advances In Computer Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the dehydration of goethite occurs through Reaction (7). However, NiCl 2 did not precipitate as an oxide, because the precipitation of FeCl 4 -in the form of Fe 2 O 3 is more thermodynamically favorable than the precipitation of Ni 2+ as NiO. So the pressure hydrochloric-acid leaching had also realized selective pressure leaching.…”
Section: Advances In Computer Sciencementioning
confidence: 99%
“…Taking for granted the stepwise gaseous reduction of haematite to metallic iron, as well as the reduction of nickel silicates into metallic nickel, it was recommended to use CO reducing gas to achieve the highest metallisation for nickel. Pournaderi et al [4] studied effects of temperature, coal amount, and reduction time on prereduction of a laterite ore (Ni 1.26%, Fe 32.6%). It was reported that the metallization of Fe was limited up to 900℃ and increased rapidly at higher temperature.…”
Section: Advances In Computer Science Research Volume 70mentioning
confidence: 99%
“…Low-grade laterite ore, which accounts for approximately 60% of the world's nickel ore reserves, has attracted much attention owing to the dwindling supply of sulphide nickel ore (Tong et al, 2013;Li et al, 2017). However, studies have shown that conventional pyrometallurgical and wet leaching processes are unsuitable for nickel recovery from low-grade nickel ores (Poumaderi et al, 2014;Quast et al, 2015;Sadowski and Pawlowska, 2017;Javanshir et al, 2018). The direct reduction magnetic separation process has proven to be a promising method to recover nickel from low-grade laterite ore (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the first step, physical losses were determined by extraction of the metallic phases with bromine-methanol solution (Pournaderi et al, 2014;Kinson, Dickeson, and Belcher, 1968) and measurement of the dissolved metals by atomic absorption spectrophotometry (AAS). In the second step, the residue from the first step was dissolved in an acid mixture (HNO 3 +HCl+HF) and the solution was analysed by AAS to determine the chemical losses in the slag.…”
Section: Volume 117mentioning
confidence: 99%
“…A gas mixture consisting of 70%N 2 -20%CO 2 -10%CO was passed through the furnace at a flow rate of 50 ml/min. Further information on the calcination and prereduction behaviour of the ore has been published previously (Keskinkılıç et al, 2012;Pournaderi et al, 2014). …”
mentioning
confidence: 99%